Eliciting guilt in virtual reality games: interplay of self-attribution, presence, and morality - Ahn, Changhyun; Noh, Ghee Young (Frontiers in Psychology, 2024)
Introduction This study investigates the psychological mechanisms in virtual reality (VR) games, focusing on the interplay between character morality, self-attribution, presence, guilt, and their collective impact on player enjoyment. Based on Affective Disposition Theory, it hypothesizes that players’ moral judgments of characters significantly affect their engagement and enjoyment of VR narratives. Methods A post-test between-subjects experiment was conducted with 97 participants to examine the influence of character morality on guilt through the mediation of self-attribution, and how these factors affect players’ sense of presence and overall enjoyment in VR games. Results The findings indicate that self-attribution significantly mediates the relationship between character morality and guilt. Additionally, the sense of presence enhances enjoyment, with a stronger sense of ‘being there’ amplifying the emotional impact of players’ moral decisions. Discussion This study highlights the full mediating effect of self-attribution in the context of VR gaming, intensifying players’ emotional responses to moral dilemmas. The results suggest that VR game designers should consider the moral implications of game narratives and character actions to create more emotionally engaging and ethically reflective gaming experiences. These insights have significant implications for VR game design and ethics, promoting greater ethical sensitivity among players.